ECTOPIC PREGNANCY AT THE UNIVERSITY OF MAIDUGURI TEACHING HOSPITAL - A TEN YEAR REVIEW - GEIDAM AD; CHAMA CM; MAIRIGA AG (Ntec Specialist, 2008)
Background: Ectopic pregnancy is a common surgical emergency in gynaecology especially in the tropics where the patients usually present with the ruptured variety with the attendant peritoneal flooding and its clinical consequences. Objectives: To determine the incidence, demographic characteristics, risk factors, clinical features, treatment, and outcomes of patients with ectopic pregnancy in our center. Methods: A descriptive study of ectopic pregnancy seen at the University of Maiduguri Teaching Hospital from January 1995 to December 2004. Results: A total of 136 cases of ectopic pregnancies occurred during this period. With the 15,120 deliveries that occurred during the same period, the overall incidence of ectopic pregnancy was 0.9/1000 deliveries (0.9%). Majority of the patients (69.8%) were between 21 to 30 years of age, 57.4% were para 1 to 4 and 86.0% were married. The duration of amenorrhoea ranged between 2 to 14 weeks with a mean of 6.9 weeks and 58.1% of the patient had a period of amenorrhoea of 5 - 8weeks. There were no historical risk factors for ectopic gestation in 30.1% of the patients but abortion, infertility, PID and previous ectopic pregnancy were found to be major risk factors. Lower abdominal pain (92.6%) was the commonest symptom and cervical excitation tenderness (51.5%) the commonest sign. The initial diagnosis was missed in 31.6% of the cases. In 69.8% the implantation site was the ampulla and the ectopic pregnancy was ruptured in 68.9% of the patients. All the patients were managed by laparatomy and the 57.4% of the patients that were transfused, were given homologous blood. There was a statistically significant association between blood transfusion and the initial packed cell volume (PCV) and the amount of haemoperitoneum found at operation. There was no maternal death and of 12 patients (8.1%) that developed complications, 8 (66.7%) had wound infection. As absence of risk factors does not in any way exclude the possibility of ectopic pregnancy as shown in this review, keeping high index of suspicion is vital in its diagnosis. Education of the populace especially women on ectopic and training and retraining of health care personnel in the management of this gynaecological emergency will reduce its occurrence and improve its management.